Malaysian Consumer Research: Does Computer Literacy Affirmative towards E-commerce Activities? - Dileep Kumar M.; Normala S. Govindarajo . (Journal of Economics and Behavioral Studies, 2015)
Rapid expansion of technology application, especially in the field of information technology, with the support of fine tune infrastructure, further correlated with severely with the ecommerce activities. This scenario is not much different in developed as well as developing countries. It is a placid trend nowadays that the customers are moving from traditional direct shopping practices to online shopping. In this scenario it is observed that the generations Y is more contented with online purchasing and adoption of e-commerce practices compare to generation X. It is hypothesized in this research that higher the computer literacy people have with higher the attitude in favor for technology adoption and ecommerce activities. Contextualizing this assumption to Malaysian scenario, fewer studies have been conducted so far and seldom any information that has shared across to the research world. Hence, a study was conducted to analyze the effect of computer literacy on internet usages and ecommerce activities among generation Y in the Malaysian context. This study provides interesting insights into the technology adoption aptitude of generation Y.